Improving Human Resource Performance Through Digital Inclusion: An Integrated Approach - Agung Budi; Irwan Prayitno; Nuraeni Nuraeni (Goodwood Publishing, 2026)
Purpose: This study aims to investigate how Talent Management, Knowledge Management, and Transformational Leadership influence Human Resource (HR) performance, specifically examining the role of digital inclusion as a mediating factor. Research Methodology: Using a quantitative associative approach, data were collected via surveys from 257 private bank employees in Banten. Statistical analyses were conducted to measure the relationships between variables. Results: The findings revealed that Talent Management and Transformational Leadership significantly boosted HR performance. Although Knowledge Management has a weaker direct impact, digital inclusion acts as a vital mediator that strengthens the positive effects of both leadership and talent strategies on overall performance. Conclusions: Digital inclusion is essential in modern HR strategies. To achieve peak performance, organizations must not only lead and manage talent effectively, but also ensure that employees are digitally integrated and competent. Limitations: This study is limited to the private banking sector in a specific geographical area (Banten), which may limit the generalizability of the results to other industries. Contributions: This research contributes to the field of strategic HR Management by highlighting the necessity of digital competencies. This study provides practical insights for banking executives and HR practitioners to prioritize digital integration for sustainable competitive advantage.